Association of lymph node metastases, grade and extent of mesenteric lymph node dissection in locoregional small intestinal neuroendocrine tumors with recurrence‐free survival. (17th November 2022) - Daskalakis, Kosmas; Wedin, Maria; Tsoli, Marina; Kogut, Angelika; Srirajaskanthan, Raj; Sarras, Konstantinos; Kattiparambil, Sajith; Giovos, George; Weickert, Martin O.; Kos‐Kudla, Beata; Kaltsas, Gregory
Abstract: We aimed to assess the prognostic impact of tumor‐ and patient‐related parameters in patients with stage I–III small intestinal neuroendocrine tumors (SI‐NETs), who underwent locoregional resective surgery (LRS) with curative intent. We included 229 patients with stage I–III SI‐NETs diagnosed from June 15, 1993, through March 8, 2021, identified using the SI‐NET databases from five European referral centers. Mean ± SD age at baseline was 62.5 ± 13.6 years; 111/229 patients were women (49.3%). All tumors were well‐differentiated; 160 were grade 1 (G1) tumors, 51 were G2, two were G3 and 18 tumors were of unspecified grade (median Ki‐67: 2%, range 1%–50%). One‐hundred and sixty‐three patients (71.2%) had lymph node (LN) involvement. The median number of retrieved lymph nodes was 10 (0–63), whereas the median number of positive LNs was 2 (0–43). After a mean ± SD follow‐up of 54.1 ± 64.1 months, 60 patients experienced disease recurrence at a median (range) of 36.2 (2.5–285.1) months. The 5‐ and 10‐year recurrence‐free survival (RFS) rates were 66.6% and 49.3% respectively. In univariable analysis, there was no difference in RFS and overall survival (OS) between LN‐positive and LN‐negative patients (log‐rank, p  = .380 and .198, respectively). However, in stage IIIb patients who underwent mesenteric lymph node dissection (MLND) with a minimum of five retrieved LN ( n  = 125), five or more LN metastases were associated with shorter RFS (median RFS [95% CI] = 107.4 [0–229.6] vs. 73.7 [35.3–112.1] months; log‐rank, p  = .048). In addition, patients with G2 tumors exhibited shorter RFS compared to patients with G1 tumors (median RFS [95% confidence interval (CI)] = 46.9 [36.4–57.3] vs. 120.7 [82.7–158.8] months; log‐rank, p  = .001). In multivariable Cox‐regression RFS analysis in stage IIIb patients, the Ki‐67 proliferation index (hazard ratio = 1.08, 95% CI = 1.035–1.131; p  < .0001) and the number of LN metastases (hazard ratio = 1.06, 95% CI = 1.001–1.125; p  = .047) were independent prognostic factors for RFS. In conclusion, LRS with a meticulous MLND and a minimum number of five harvested LNs appears to be critical in the surgical management of SI‐NET patients with locoregional disease. In patients who underwent LRS and MLND, the Ki‐67 proliferation index and the LN metastases count were independent predictors of RFS. Abstract : In the present study, we assess survival outcomes of patients with small intestinal neuroendocrine tumors (SI‐NET) and locoregional disease only, after locoregional resective surgery (LRS) with curative intent. We demonstrate that the majority of SI‐NET patients without distant metastases, who undergo LRS, have lymph‐node (LN) metastases. Although we were not able to confirm a difference in recurrence‐free survival (RFS) between LN‐positive and LN‐negative patients, in the subset of LN‐positive patients who undergo mesenteric lymph‐node dissection (MLND) with a minimum of 5 retrieved LN, 5 or more LN metastases are indeed associated with shorter RFS. In addition, patients with G2 tumors exhibit shorter RFS compared to patients with G1 tumors. In multivariable analysis, the number of LN metastases and the Ki67 proliferation index are found to be predictors of RFS among patients with locoregional disease, when a sufficient MLND with 5 or more harvested mesenteric LN is performed. Therefore, a surgical approach of meticulous MLND with a minimum of 5 harvested LNs combined with mesentery‐sparing surgery to preserve intestinal length when feasible should probably be performed routinely in patients with evident nodal metastases. In the era of personalized NET management, our findings may provide a stratified model for disease prognostication to predict recurrence after primary locoregional resective surgery and guide the extent of mesenteric lymph‐node dissection.